Magia, trasformazione e divinità femminili nelle fonti nordiche - Lombardi, Maria Cristina (Studi e materiali di storia delle religioni, 2012)
In this paper I will suggest that transformation is an important aspect of Nordic mythology related to pagan religious beliefs and magical rites in Old Norse culture. My main sources for this investigation will be some Eddic lays, scaldic stanzas and prose passages in Fornaldarsögur, especially in Friðþjófs saga where relationships between pagan religion and magic rites are quite evident. A positive and a negative sorcery seem to have existed side by side both using transformation and shape-changing. These aspects probably did not possess so sinister connotations in Scandinavian sources as they had in the Southern European ones, probably because of Odin 's strong connections with sorcery and shape-changing. As an example of this, I shall examine the translation of one Marie de France's lais into Old Norse which shows how, compared to the original, the phenomenon is viewed in a different way. (English)